2021
DOI: 10.1115/1.4051208
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Chemical Composition and Moisture Sensitivity in LiNixMnyCo1−XYO2 for Lithium-Ion Batteries

Abstract: Chemical composition – moisture sensitivity relationship of LiNixMnyCo1-x-yO2 (NMC) cathode materials was investigated by exploring crystal structures, surface properties and electrochemical performance behaviors of various commercial NMC powders: LiNi1/3Mn1/3Co1/3O2 (NMC111), LiNi0.5Mn0.3Co0.2O2 (NMC532), LiNi0.6Mn0.2Co0.2O2 (NMC622), and LiNi0.8Mn0.1Co0.1O2 (NMC811). The NMC powders were stored in different moisture conditions: moisture-free, humidified air, or immersed in water. Rietveld refinement analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In contrast to the bare NMC cathodes, the cathodes blended with LLTO demonstrated more stable voltage profiles and exhibited relatively lower voltage drops during the 300 cycles. The d Q /d V profiles of both the NMC811 + 1 wt % LLTO and NMC811 + 5 wt % LLTO cathodes exhibited distinct peaks at around 3.7, 3.8, and 4.25 V vsLi , which are associated with multiple phase transformations [i.e., H1 – >monoclinic (M) – >H2 – >H3] of NMC . The enhanced performance of the LLTO–NMC811 cathodes can be attributed to two primary factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the bare NMC cathodes, the cathodes blended with LLTO demonstrated more stable voltage profiles and exhibited relatively lower voltage drops during the 300 cycles. The d Q /d V profiles of both the NMC811 + 1 wt % LLTO and NMC811 + 5 wt % LLTO cathodes exhibited distinct peaks at around 3.7, 3.8, and 4.25 V vsLi , which are associated with multiple phase transformations [i.e., H1 – >monoclinic (M) – >H2 – >H3] of NMC . The enhanced performance of the LLTO–NMC811 cathodes can be attributed to two primary factors.…”
Section: Resultsmentioning
confidence: 99%
“…In a prior study, we reported that full-cells with nickel-rich layered cathodes and graphite anodes demonstrated poor cyclability, particularly at higher nickel content and higher operating voltages. 21,28 Full-cell cycles at high voltage resulted in a series of phase transitions and associated mechanical stress and parasitic reactions at the CEI for the cathodes. The resulting byproducts such as dissolved transition metals (such as Mn and Ni ions) and HF migrate to anodes by an electric field and attack the graphite SEI, leading to destabilization of the SEI and triggering additional parasitic reactions.…”
Section: Effect Of Llto On High-voltage Performances Of Nmc811mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that the moisture and prolonged storage of these electrodes results in a severe accumulation of surface carbonates. 47,48 The carbonate species produced during ambient exposure of NMC 811 are electrochemically inactive with poor electronic conductivity, which hinders Li diffusion significantly, 49,50 resulting in the capacity fade as seen in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we address the aforementioned issues of ambient-reactive Ni-rich layered oxides via a hydrophobic coating layer composed of graphene and ethyl cellulose (GrEC). We demonstrate this scheme for LNO because it represents the Ni-rich limit with the highest ambient sensitivity in the family of Ni-rich layered oxides. ,, Ethyl cellulose (EC) is an attractive materials choice because it is hydrophobic and can be scalably coated onto cathode material surfaces via solution-phase methods. EC can also be pyrolyzed thermally or photonically, enabling its removal immediately preceding electrochemical cycling.…”
Section: Introductionmentioning
confidence: 99%